Understanding the Employment Expectations of Young Professionals: A Study by Education Level - Szabó-Szentgróti, Gábor; Martin , Gelencsér; Hollósy-Vadász , Gábor; Kőmüves , Zsolt (Journal of Ecohumanism, 2024)
Young employees have to make many trade-offs in their job search and are often confronted with a lack of skills and abilities. In our survey, we investigated the expectations of young employees towards employers in relation to their level of education and the factors that influence/inhibit their job placement. The results confirmed that remuneration, motivation, an inspiring work environment and career opportunities offered by employers play a major role in job choice. The young employees’ responses showed that they feel underprepared for the challenges of the labor market and see the solution to this problem in increasing the number of practical training hours. The study highlights the differences in the expectations of students at different levels of education and could be a starting point for further research.